Countdown 1945 the extraordinary story of the atomic bomb and the 116 days that changed the world - Wallace, Chris 1947-; Weiss, Mitch (Avid Reader Press, in imprint of Simon & Schuster, Inc., 2020)
A "behind-the-scenes account of the 116 days leading up to the Americans attack on Hiroshima"--Dust jacket flap
Illustrations on endpapers
Keywords: Geschichte 1945; Kernwaffe; Zweiter Weltkrieg; Hiroshima; USA; Hiroshima-shi (Japan) / History / Bombardment, 1945; United States / Foreign relations / Japan; Atomic bomb / United States / History; World War, 1939-1945; HISTORY / Military / World War II.; HISTORY / Modern / 20th Century; HISTORY / United States / 20th Century; HISTORY / Asia / Japan; Atomic bomb; Diplomatic relations; Japan; Japan / Hiroshima-shi; United States; Hiroshima-shi (Japan) / History; United States / Foreign relations; 1939-1945; History